PERAN KEMITRAAN BISNIS DALAM MENINGKATKAN DAYA SAING UMKM X BLITAR - Elizza Destyana Fitri; Arif Wahyudi (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya, 2026)
Increasing competition in the garment industry requires MSMEs to adopt effective strategies to maintain their competitiveness. Business partnerships are essential as they provide access to resources, market information, and opportunities for business development. This study aims to describe the role of business partnerships in enhancing the competitiveness of X, a garment MSME in Blitar Regency. A descriptive qualitative method was applied, using in-depth interviews with the business owner and direct observations of production activities and partnership practices. The findings reveal that partnerships with schools, clothing stores, regular customers, and other business actors contribute positively through four main mechanisms: operational stability through demand predictability, product innovation through direct feedback from partners, market expansion through word-of-mouth effects where approximately 70% of new customers come from partner recommendations, and operational efficiency through improved capacity utilization from 60% to 80-85%. The study found that informal trust-based partnerships prove to be an effective model in the local MSME context, providing high flexibility and reducing transaction costs associated with formal contracts. However, challenges such as limited skilled labor, potential miscommunication, and limited raw material availability remain present. In conclusion, business partnerships play a crucial role in strengthening MSME competitiveness and business sustainability, and these findings highlight the importance of developing mutually beneficial partnerships as a strategic approach for MSMEs.